SN 2023tsz: a helium-interaction-driven supernova in a very low-mass galaxy - Warwick, B.; Lyman, J.; Pursiainen, M.; Coppejans, D. L.; Galbany, L.; Jones, G. T.; Killestein, T. L.; Kumar, A.; Oates, S. R.; Ackley, K.; Anderson, J. P.; Aryan, A.; et al. (Oxford University Press (OUP), 2025)
SN 2023tsz is a Type Ibn supernova (SN Ibn), an uncommon subtype of stripped-envelope core-collapse supernovae (SNe), discovered in an extremely low-mass host. SNe Ibn are characterized by narrow helium emission lines in their spectra and are believed to originate from the collapse of massive Wolf-Rayet (WR) stars, though their progenitor systems still remain poorly understood. In terms of energetics and spectrophotometric evolution, SN 2023tsz is largely a typical example of the class, although line profile asymmetries in the nebular phase are seen, which may indicate the presence of dust formation or unshocked circumstellar material. Intriguingly, SN 2023tsz is located in an extraordinarily low-mass host galaxy that is in the second percentile for stripped-envelope SN host masses and star formation rates (SFRs). The host has a radius of 1.0 kpc, a g-band absolute magnitude of -12.72 +/- 0.05, and an estimated metallicity of log(Z(*)/Z(circle dot)) approximate to -1.6. The SFR and metallicity of the host galaxy raise questions about the progenitor of SN 2023tsz. The low SFR suggests that a star with sufficient mass to evolve into a WR would be uncommon in this galaxy. Further, the very low metallicity is a challenge for single stellar evolution to enable H and He stripping of the progenitor and produce an SN Ibn explosion. The host galaxy of SN 2023tsz adds another piece to the ongoing puzzle of SNe Ibn progenitors, and demonstrates that they can occur in hosts too faint to be observed in contemporary sky surveys at a more typical SN Ibn redshift.